Androgen receptor signaling and pyrethroids: Potential male infertility consequences - Sheikh, Ishfaq Ahmad; Beg, Mohd Amin; Hamoda, Taha Abo-AlmagdAbdel-Meguid; Mandourah, Hammam Mahmoud Siraj; Memili, Erdogan (Frontiers in Cell and Developmental Biology, 2023)
Infertility is a global health concern inflicting considerable burden on global economy along with a severe socio-psychological impact. About 15% of couples are suffering from infertility globally with male factor contribution of approximately 50%. However, the male infertility remains unexplored to a large extent as the burden of infertility is mostly assigned to women. Endocrine disrupting chemicals (EDCs) have been proposed to be one of the factors causing male infertility. Pyrethroids represent an important class of EDCs and numerous studies have associated the pyrethroid exposure with impaired male reproductive function and development. Therefore, present study was performed to investigate the potential toxic effects of two common pyrethroids, cypermethrin and deltamethrin, on androgen receptor (AR) signaling. The structural binding characterization of cypermethrin and deltamethrin against AR ligand binding pocket was performed using Schrodinger’s induced fit docking (IFD) approach. Various parameters such as binding interactions, binding energy, docking score, and IFD score were estimated. Furthermore, the AR native ligand, testosterone was also subjected to similar experiments against AR ligand binding pocket. The results revealed commonality in the amino-acid binding interactions and overlap in other structural parameters between the AR native ligand, testosterone, and the ligands, cypermethrin and deltamethrin. The estimated binding energy values of cypermethrin as well as deltamethrin were very high and close to the values calculated for AR native ligand, testosterone. Taken together, the results of this study suggested potential disruption of AR signaling by cypermethrin and deltamethrin which may result in androgen dysfunction and subsequent male infertility.